2017
DOI: 10.1039/c7ta06453e
|View full text |Cite
|
Sign up to set email alerts
|

A general strategy towards carbon nanosheets from triblock polymers as high-rate anode materials for lithium and sodium ion batteries

Abstract: Carbon nanosheets from triblock polymers behave well as anode materials for lithium- and sodium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 89 publications
4
67
1
Order By: Relevance
“…There were two diffraction peaks centered at ca. [6,22] These results indicated that the PI had been successfully converted to amorphous after carbona nnealing process 23 .T his finding was further elucidated by the Fouriert ransform infrared (FTIR) spectra of the composites before anda fter carbonization treatment ( Figure 3b). [6,21] In contrast, only the broad peak at ca.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…There were two diffraction peaks centered at ca. [6,22] These results indicated that the PI had been successfully converted to amorphous after carbona nnealing process 23 .T his finding was further elucidated by the Fouriert ransform infrared (FTIR) spectra of the composites before anda fter carbonization treatment ( Figure 3b). [6,21] In contrast, only the broad peak at ca.…”
Section: Resultsmentioning
confidence: 78%
“…[1,2] Despite these advantages, the limited lithium resource on earth restricts the applications of LIBs severely.I nview of this, researchers have made great efforts to explore alternative energy storages ystems. [5,6] However,o nly a few anode materials are suitable for SIB, because of larger radius of Na than Li, which would suffer from more serious volumee xpansion during the charge/discharge process and lead to more sluggish sodium kinetics, more difficult intercalation into the lattice andl ower diffusion in the electrode materials. [5,6] However,o nly a few anode materials are suitable for SIB, because of larger radius of Na than Li, which would suffer from more serious volumee xpansion during the charge/discharge process and lead to more sluggish sodium kinetics, more difficult intercalation into the lattice andl ower diffusion in the electrode materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations